Strategies in Primary Care to Face the SARS-CoV-2 / COVID-19 Pandemic: An Online Survey - Eisele, Marion; Pohontsch, Nadine Janis; Scherer, Martin (Frontiers in Medicine, 2021)
Background: Primary care plays a key role in pandemics like the SARS-CoV-2 pandemic in 2020. We aimed to investigate the challenges faced and the solutions implemented in primary care. Methods: 121 general practitioners in Germany completed the online survey. We used open questions to examine challenges experienced and solutions implemented during the early pandemic and chose qualitative content analysis to extract and describe the meaning of the answers. We derived deductive categories from the research questions and formed inductive categories during the material reviews. Results: Main challenges were: insufficient information, lack of protective equipment, need to restructure practice procedures and insufficient individual and structural pandemic preparedness, resulting in secondary challenges: fear of infection, impaired patient care, aggravated steering of patients, difficult cooperation with external entities and a not viable hygiene concept advised by authorities. Strategies to address these challenges included establishing regular team-meetings to develop new solutions, focusing on few reliable sources of information, working in alternating shifts, increasing telemedicine, establishing window and open-air practices and building networks with other health care providers. Respondents criticised the lack of consideration of their experiences in planning pandemic measures within primary care. Conclusions: General practitioners successfully applied pragmatic and creative strategies in their practices during the early phase of the pandemic. Among these, communication within and between practices emerged as a key strategy. These strategies should be provided with pandemic preparedness plans. The lacking consideration of the primary care providers’ experiences in planning and implementing pandemic measures needs to be addressed by stakeholders.